2017
DOI: 10.5500/wjt.v7.i2.144
|View full text |Cite
|
Sign up to set email alerts
|

Systemic meta-analysis assessing the short term applicability of early conversion to mammalian target of rapamycin inhibitors in kidney transplant

Abstract: AIMTo consolidate the present evidence of effectiveness in renal functioning and graft survival following early introduction of mammalian target of rapamycin (mTOR) inhibitors with or without calcineurin inhibitors (CNIs) in renal transplant recipients.METHODSWe analysed the current literature following PROSPERO approval describing the role of immunosuppressive agent, mTOR inhibitors as an alternative to CNI within six months of renal transplant by searching the PubMed, EMBASE, Cochrane, Crossref, and Scopus u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…These strategies include CNI minimization, conversion, avoidance, and withdrawal by using mammalian target of rapamycin (mTOR) inhibitor or belatacept. Systematic reviews and meta-analyses consistently demonstrated that mTOR inhibitors and belatacept are associated with favorable renal allograft function but associated higher risk of rejection [95,96].…”
Section: Special Consideration To Prevent and Mitigate Failing Renal Allograftmentioning
confidence: 99%
“…These strategies include CNI minimization, conversion, avoidance, and withdrawal by using mammalian target of rapamycin (mTOR) inhibitor or belatacept. Systematic reviews and meta-analyses consistently demonstrated that mTOR inhibitors and belatacept are associated with favorable renal allograft function but associated higher risk of rejection [95,96].…”
Section: Special Consideration To Prevent and Mitigate Failing Renal Allograftmentioning
confidence: 99%